Efficacy and safety of transarterial chemoembolization plus antiangiogenic- targeted therapy and immune checkpoint inhibitors for unresectable hepatocellular carcinoma with portal vein tumor thrombus in the real world - Feng, Jin-Kai; Liu, Zong-Han; Fu, Zhi-Gang; Chai, Zong-Tao; Sun, Ju-Xian; Wang, Kang; Cheng, Yu-Qiang; Zhu, Hong-Fei; Xiang, Yan-Jun; Zhou, Li-Ping; Shi, Jie; Guo, Wei-Xing; et al. (Frontiers in Oncology, 2022)
Purpose: This study aimed to assess the efficacy and safety of a triple therapy comprising of transarterial chemoembolization (TACE), anti-angiogenic targeted therapy and PD-1 inhibitors in a real-world cohort of patients with unresectable hepatocellular carcinoma (HCC) with portal vein tumor thrombus (PVTT). Methods: Consecutive patients treated with TACE combined with anti-angiogenic therapy and PD-1 inhibitors at the Eastern Hepatobiliary Surgery Hospital Between June 2019 and May 2021 were enrolled. Baseline characteristics and treatment course of the patients were recorded. Tumor response was evaluated based on the Response Evaluation Criteria in Solid Tumors (RECIST) 1.1 and HCC-specific modified RECIST (mRECIST). Overall survival (OS) and progression-free survival (PFS) of the patients were analyzed using the Kaplan-Meier method. Adverse events (AEs) were assessed according to National Cancer Institute Common Terminology Criteria for Adverse Events version 5.0. Results: As of the data cutoff on August 30th, 2021, the median follow-up time was 10.0 (3.9–28.4) months. Thirty-nine eligible patients were included. The objective response rate (ORR) and disease control rate (DCR) were 35.9% and 74.4% according to the RECIST 1.1, and 48.7% and 84.6% according to mRECIST criteria. The median OS and PFS were 14.0 and 9.2 months, respectively. Moreover, 34 (87.2%) patients experienced at least one treatment-related AE, 8 (20.5%) patients experienced grade 3/4 treatment-related AEs. The most common treatment- and laboratory-related AE were hypertension (46.2%) and decreased albumin (53.8%), respectively. No treatment-related mortality occurred during the study period. Conclusions: TACE combined with antiangiogenic targeted therapy and immune checkpoint inhibitors may have promising anti-cancer activity in unresectable HCC patients with PVTT. AEs were manageable, with no unexpected overlapping toxicities.